Dorsomedial hypothalamus mediates autonomic, neuroendocrine, and locomotor responses evoked from the medial preoptic area - Hunt, Joseph L. (American Physiological Society, 2010)
Previous studies suggest that sympathetic responses evoked from the preoptic area in anesthetized rats require activation of neurons in the dorsomedial hypothalamus. Disinhibition of neurons in the dorsomedial hypothalamus in conscious rats produces physiological and behavioral changes resembling those evoked by microinjection of muscimol, a GABA(A) receptor agonist and neuronal inhibitor, into the medial preoptic area. We tested the hypothesis that all of these effects evoked from the medial preoptic area are mediated through neurons in the dorsomedial hypothalamus by assessing the effect of bilateral microinjection of muscimol into the DMH on these changes. After injection of vehicle into the dorsomedial hypothalamus, injection of muscimol into the medial preoptic area elicited marked increases in heart rate, arterial pressure, body temperature, plasma ACTH, and locomotor activity and also increased c-Fos expression in the hypothalamic paraventricular nucleus, a region known to control the release of ACTH from the adenohypophysis. Prior bilateral microinjection of muscimol into the dorsomedial hypothalamus produced a modest depression of baseline heart rate and body temperature but completely abolished all changes evoked from the medial preoptic area. Microinjection of muscimol just anterior to the dorsomedial hypothalamus had no effect on autonomic and neuroendocrine changes evoked from the medial preoptic area. Thus, activity of neurons in the dorsomedial hypothalamus mediates a diverse array of physiological and behavioral responses elicited from the medial preoptic area, suggesting that the latter region represents an important source of inhibitory tone to key neurons in the dorsomedial hypothalamus.